KNOWLEDGE AND PERCEPTIONS OF SELF-MEDICATION PRACTICES IN AN URBAN COMMUNITY - VARGHESE SNEHA SUJA,; SNEHA DUTTA,; ANN MARY SWAROOP, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: This study was conducted with the aim to assess the knowledge and attitude of self-medication practices among the residents of an urban community. Methods: A cross-sectional, observational study was conducted among 270 participants for the duration of 6 months using a semi-structured questionnaire which consisted of the domains of knowledge and attitude. Logistic regression was used for drawing statistical inferences. Results: The prevalence of self-medication was found to be 37.04%. It was found that 73.33% of the respondents were aware of the term “self-medication” and their major source for information was obtained through acquaintances (44.44%). About 68.55% of the participants agreed that self-medication is a part of taking care of oneself and it needs to be encouraged. Overall, the participants had a good knowledge and positive attitude toward the practice of self-medication. Conclusion: This study mainly focuses on improving the subjects’ knowledge, thereby bringing changes in the attitude and practice toward disease management. Understanding the subjects’ level of knowledge and attitude will enable a more efficient process for creating an awareness among the public to ensure its safe and responsible use.